Budaya Berbagi dalam Filantropi Islam: Kajian atas Praktik Kedermawanan di Komunitas Muslim - Putra, Muhammad Deni; Afandi, Mukhamad Yazid; Fadilla, Siti; Mansur, Muhammad; Argantara, Zaid Raya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study examines the role of the culture of sharing in Islamic philanthropy, particularly the practice of generosity among Muslim communities, using a qualitative approach through literature review. The aim is to understand how the culture of sharing, social character, and local religious and cultural values influence the collection and distribution of zakat and charity. Findings indicate that the culture of sharing in Muslim societies significantly contributes to increased awareness and participation in philanthropic activities. Communities that uphold the values of solidarity and mutual assistance are more active in collecting and distributing zakat and charity, creating strong social networks. The analysis of social and cultural character reveals that local norms, such as the tradition of helping one another, influence patterns of generosity and strengthen social bonds among community members. Furthermore, religious values, including sincerity and the obligation of zakat, serve as primary motivations for individuals to engage in philanthropy. This research emphasizes the importance of integrating religious values and local culture into charitable programs, where philanthropic institutions that consider community needs are more likely to succeed in attracting participation. The findings are expected to serve as a foundation for developing policies and strategies to strengthen philanthropic practices in Muslim communities and enhance solidarity and social welfare. Additionally, this study suggests the need for further exploration of the relationship between the culture of sharing and the effectiveness of philanthropy in a broader context.Keywords: Culture of Sharing, Islamic Philanthropy, Generosity, Muslim Community